Multiscale Structural Gel Polymer Electrolytes with Fast Li+ Transport for Long‐Life Li Metal Batteries. (30th October 2022) - Yang, Hai Xia; Liu, Zhi Kang; Wang, Yu; Li, Nian Wu; Yu, Le
Abstract: Li metal batteries (LMBs) are considered as promising candidates for future rechargeable batteries with high energy density. However, Li metal anode (LMA) is extensively sensitive to general liquid electrolytes, leading to unstable interphase and dendrites growth. Herein, a novel gel polymer electrolyte consisting of a micro‐nanostructured poly(vinylidene fluoride‐ co ‐hexafluoropropylene) matrix and inorganic fillers of Zeolite Socony Mobil‐5 (ZSM‐5) and SiO2 nanoparticles, is fabricated to expedite Li + ions transport and suppress Li dendrite growth. Due to the Lewis acid interaction, SiO2 can absorb amounts of PF6 − and promote the dissociation of LiPF6 . The specific sub‐nanometer pore structure of ZSM‐5 greatly enhances the Li + ion transference number. These structures can restrain the decomposition of electrolytes and build stable interphase on LMA. Therefore, the Li||Ni0.8 Co0.1 Mn0.1 O2 full cell maintains 92% capacity retention after 300 cycles at 1 C (1 C ≈190 mAh g −1 ) in carbonate electrolyte. This multiscale design provides an effective strategy for electrolyte exploration in high‐performance LMBs. Abstract : Multiscale Structural Gel Polymer Electrolytes (GPEs), including micrometer‐scale poly(vinylidene fluoride‐ co ‐hexafluoropropylene) matrix, SiO2 nanoparticles, Zeolite Socony Mobil‐5 with a sub‐nanometer channel, Li salt, and carbonate ester, are fabricated for Li metal batteries. The multiscale structural GPEs can expedite Li + ions transport and build stable interphase on Li metal anodes, thereby reducing Li dendrite growth and delivering outstanding electrochemical performance.